Illocutionary Acts in Collider Interviews with the Jamojaya Film Crew (Sastra Inggris UNPAM, 2024)
This study aims to analyze the types and functions of illocutionary speech acts in interviews with Rich Brian and Justin Chon. It further identifies the most and least frequently used illocutionary acts in the interview. Using a descriptive-qualitative approach, this analysis relies on data drawn from a video interview with the cast and crew of Jamojaya on the Collider Interviews YouTube channel. The analysis is based on the framework developed by Searle & Vanderveken (1985). The data, transcribed into written form, was observed and categorized into various types and functions of illocutionary acts. Out of 139 instances of illocutionary acts identified, the breakdown is as follows: 85 assertive acts (61.15%), 33 directives (23.74%), 20 expressives (14.39%), 1 commissive (0.72%), and 0 declaratives. These findings suggest that assertive acts are the most prevalent, encompassing functions like informing, believing, stating, and asserting, which dominate the interview. Conversely, declaratives are the least represented category in this study.